INNOVATIVE APPROACHES AND INTEGRATED MANAGEMENT METHODOLOGY FOR THE DEVELOPMENT OF MARKETING ACTIVITIES IN HIGHER EDUCATION INSTITUTIONS (Marketing Journal, 2025)
The article explores innovative approaches to improving marketing activities in higher education institutions. The analysis identified the interrelation of project -based learning, digital technologies, communication strategies, international collaboration, and knowledge management, leading to the development of a conceptual model. The findings provide scientifically grounded recommendations for forming effective marketing strategies, strengthening university branding, and enhancing competitiveness.
Keywords: higher education; marketing; innovative learning; digital technologies; international collaboration; brand image